2015
DOI: 10.1111/bph.13274
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 promotes epithelial cell transformation and breast tumourigenesis via induction of PIN1 gene expression

Abstract: BACKGROUND AND PURPOSEDipeptidyl peptidase 4 (DPP4) is an aminopeptidase that is widely expressed in different cell types. Recent studies suggested that DPP4 plays an important role in tumour progression in several human malignancies. Here we have examined the mechanisms by which up-regulation of DPP4 expression causes epithelial transformation and mammary tumourigenesis. EXPERIMENTAL APPROACHExpression of DPP4 and the peptidylprolyl cis/trans isomerase, NIMA-interacting 1 (PIN1), and the cytotoxic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…A retrospective cohort study assessed the risk of prostate cancer associated with sitagliptin, also using the Taiwanese database of the National Health Insurance between 1999 and 2000, and the result of HR = 0.613 (95% CI = 0.493–0.763) showed that sitagliptin could significantly reduce the risk of prostate cancer 49 . Some in vivo studies explored the effect of DPP4 on tumorigenesis of the breast, ovary and prostate at the molecular level; however, it was not conclusive whether DPP4 promoted tumorigenesis 50 – 52 .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study assessed the risk of prostate cancer associated with sitagliptin, also using the Taiwanese database of the National Health Insurance between 1999 and 2000, and the result of HR = 0.613 (95% CI = 0.493–0.763) showed that sitagliptin could significantly reduce the risk of prostate cancer 49 . Some in vivo studies explored the effect of DPP4 on tumorigenesis of the breast, ovary and prostate at the molecular level; however, it was not conclusive whether DPP4 promoted tumorigenesis 50 – 52 .…”
Section: Discussionmentioning
confidence: 99%
“…B cells can mediate local effects, such as antigen presentation, cytokine release and cell–cell contact regulated by costimulatory molecules, and systemic effects via antibodies. Like CD4 + T cells, B cells secrete pro‐fibrotic cytokines that contribute to liver fibrosis and induce the differentiation of HSC into myofibroblasts 2 , 22 . These myofibroblasts could in turn increase the synthesis of collagen and tissue inhibitor of matrix metalloproteinase.…”
Section: Discussionmentioning
confidence: 99%
“…Like CD4 + T cells, B cells secrete pro-fibrotic cytokines that contribute to liver fibrosis and induce the differentiation of HSC into myofibroblasts. 2,22 These myofibroblasts could in turn increase the synthesis of collagen and tissue inhibitor of matrix metalloproteinase. B cell function has been associated with fibrosis in human skin and lung.…”
Section: Role Of Dpp4 In Fibrosis Xm Wang Et Almentioning
confidence: 99%
“…Similarly, the role of CD26/DPP4 in breast cancer remains poorly understood. In-vitro studies demonstrated thatinhibition of CD26/DPP4 stimulated breast cancer metastasis, likely via induction of CXCL12/CXCR4 (10), while others reported inhibition of CD26/DPP4 led to the suppression of breast cancer tumor growth (11). To evaluate the role of CD26/DPP4 inhibition in clinical setting, we conducted a retrospective analysis of patients with advanced airway and colorectal cancers with diabetes who were taking DPP4i (12).…”
Section: Introductionmentioning
confidence: 99%